Introducing context in SEW research: challenges and opportunities - Mazen Batterjee, Mohamed (IE University, 2022)
Based on a sample of family firms from five diverse countries, this empirical exploratory study investigates noneconomic driver represented by socioemotional wealth (SEW) across cultures. SEW refers to the pursuit of affective endowment by family firms and has been recently emphasized to be the main reference point for family firms. Despite the popularity of SEW, there has been concerns regarding its validity as a construct. Since SEW is deeply rooted in family firms; it is thus suggested to be highly influenced by contextual settings, this study suggests that one way to enhance SEW research is by contextualizing it. A random sample was obtained from family firms in Saudi Arabia, Spain, Mexico, Vietnam and Canada through a number of relevant data bases. The data was collected from chairmen and CEOs of firms who were also family members. A multi-group comparison and a linear regression were performed to explore the differences in SEW across cultures as well as the moderating effect of cultures on the relationship between SEW and performance. Findings suggests that SEW varies across cultures. Some SEW dimensions were found to be different across some cultural groups, while the “Emotional Attachment” showed to be consistently different across all cultural groups. The research also shows that culture moderates the relationship between SEW and performance. It was found to be significant and positive in societies with high power distance and low individualism. It was found to be insignificant in cultures characterized with low power distance and high individualism. The research contributes to the SEW research by exploring the relationship between context, SEW and performance thus helping in highlighting possible reasons of why previous research has been inconclusive regarding SEW and its relationship to performance.   By comparing SEW across cultures, we notice the possibility that the underlying logic of the SEW approach might not be standard across contexts. To the researcher’s knowledge, contextualizing SEW research as a way to enhance knowledge of the field and addressing its criticism, has not been done despite its high relevance. Thus, the research addresses this perceived gap. In addition, the research makes a methodological contribution by confirming measurement invariance of the FIBER conceptualization of SEW, thus confirming its universal applicability. Finally, this research contributes to the understanding of the heterogeneity of family firms by highlighting the differences of SEW among them which is more evident across cultures. This study asserts the importance of contextualizing SEW research by demonstrating the variation in SEW and in its relationship with firm’s outcomes. It also provides samples of how to conduct context by sampling and context by comparing research and offers them a validated conceptualization of SEW construct. It opens new avenues of research by providing research agenda on how to further develop the research through context by theorizing.
Introducción del contexto en la investigación SEW: retos y oportunidades.
El presente estudio empírico exploratorio, basado en una muestra de empresas familiares de cinco países distintos, investiga el motor no económico representado por la riqueza socioemocional (SEW por sus siglas en inglés) en las distintas culturas. La SEW hace referencia a la búsqueda de la dotación afectiva por parte de las empresas familiares y se ha destacado recientemente como el principal referente para las empresas familiares. A pesar de la popularidad de la SEW, se ha puesto en entredicho su validez como constructo. Dado que la SEW goza de un profundo arraigo en las empresas familiares, se sugiere que está muy expuesta a la influencia de aspectos contextuales. Así, el presente estudio sugiere que una forma de mejorar la investigación de la SEW es contextualizándola. Se obtuvo una muestra aleatoria de empresas familiares de Arabia Saudí, España, México, Vietnam y Canadá a través de una serie de bases de datos relevantes. Los datos se obtuvieron de los presidentes y CEO de las empresas que también eran miembros de la familia. Se realizó una comparación multigrupo y una regresión lineal para explorar las diferencias de SEW entre culturas, así como el efecto moderador de las culturas en la relación entre SEW y rendimiento. Los resultados sugieren que la SEW varía entre culturas. Algunas dimensiones de la SEW resultaron ser diferentes en algunos grupos culturales, mientras que el ¿apego emocional¿ mostró diferencias sistemáticas en todos los grupos culturales. La investigación también muestra que la cultura modera la relación entre la SEW y el rendimiento. Se comprobó que era significativo y positivo en las sociedades con elevada distancia de poder y bajo individualismo. En cambio, resultó ser insignificante en las culturas caracterizadas por una baja distancia de poder y un alto individualismo. El estudio contribuye a la investigación sobre la SEW al explorar la relación entre el contexto, la SEW y el rendimiento, con lo que ayuda a destacar las posibles razones por las que las investigaciones anteriores no han sido concluyentes en cuanto a la SEW y su relación con el rendimiento. Al comparar la SEW entre culturas, observamos la posibilidad de que la lógica subyacente del enfoque de la SEW no sea estándar en todos los contextos. Por lo que sabe el investigador, no se ha hecho una contextualización de la investigación sobre la SEW como forma de mejorar el conocimiento del campo y abordar sus críticas, a pesar de su gran relevancia. La investigación, por tanto, aborda esta laguna percibida. Además, la investigación hace una contribución metodológica al confirmar la invarianza de medición de la conceptualización FIBER de la SEW, lo que confirma así su aplicabilidad universal. Por último, esta investigación contribuye a la comprensión de la heterogeneidad de las empresas familiares al poner de relieve las diferencias de la SEW entre ellas, que son más evidentes en las distintas culturas. Este estudio afirma la importancia de contextualizar la investigación sobre la SEW demostrando la variación de esta y su relación con los resultados de la empresa. También proporciona muestras de cómo llevar a cabo investigaciones de contexto muestral y de contexto comparativo y les ofrece una conceptualización validada del constructo SEW. Abre nuevas vías de investigación al proporcionar una agenda de investigación sobre cómo seguir desarrollando la investigación a través del contexto teórico.
Keywords: SEW; FIBER; Context; Measurement invariance; Emoción; 6301 Sociología Cultural; 6309 Grupos Sociales; 5311 Organización y Dirección de Empresas